Mr Majeika - Carpenter, Humphrey; Rogers, Frank (London, Puffin books, 2007)
Magic carpets don't turn up in schools, but this is exactly what happens when Class Three's new teacher flies in through the classroom window. With Mr Majeika in charge, suddenly life at school becomes much more exciting!
Keywords: English fiction